Integrin Signaling in Oligodendrocytes and Its Importance in CNS Myelination - O'Meara, Ryan W. (Hindawi Publishing Corporation, 2011)
Multiple sclerosis is characterized by repeated demyelinating attacks of the central nervous system (CNS) white matter tracts. To tailor novel therapeutics to halt or reverse disease process, we require a better understanding of oligodendrocyte biology and of the molecular mechanisms that initiate myelination. Cell extrinsic mechanisms regulate CNS myelination through the interaction of extracellular matrix proteins and their transmembrane receptors. The engagement of one such receptor family, the integrins, initiates intracellular signaling cascades that lead to changes in cell phenotype. Oligodendrocytes express a diverse array of integrins, and the expression of these receptors is developmentally regulated. Integrin-mediated signaling is crucial to the proliferation, survival, and maturation of oligodendrocytes through the activation of downstream signaling pathways involved in cytoskeletal remodeling. Here, we review the current understanding of this important signaling axis and its role in oligodendrocyte biology and ultimately in the myelination of axons within the CNS.